التنظيم القانوني لعقد البث الإذاعي والتلفزيوني عبر الأقمار الصناعية : دراسة مقارنة - جلال، ناصر خليل; قادر، كامران محمد (جامعة كركوك - كلية القانون والعلوم السياسية, 2014)
The developments in the communication technology sector have had their impact on the legal side, and the emergence of new legal relations. Among these developments, which has been reached the possibility of broadcasting via satellites. The quality of radio and television broadcasting via satellite and covering large geographical space is one of the justifications that push radio and television broadcasting institutions to choose this route for the conduction of their programs for the followers. Actually that broadcast institutions cannot do it just through a contract with the owner of the satellite. In this regard, we cannot find any regulation for this contract by the legislature. In addition, we observe the impact of the absence of the Telecommunications Act in Iraq and the draft of Iraqi Communications and Media Commission Act, which the parliament is still working on despite the preparation process has been going on for years. The broadcasting via satellite in terms of concept, characteristics and adaptation, as well as the obligations of each owner of satellite and broadcasting institution will limit the scope of the study. Thus, we see the study of the subject through the two sections. In the first section, we illustrate the concept of the contract of radio and television broadcasts via satellite and we explain, and in the second section, we discuss the obligations of the contract parties.
Keywords: وسائل الإعلام -- الإذاعة والتلفزيون -- القوانين والتشريعات -- العقودات القانونية -- البث الإذاعي والتلفزيوني -- الأقمار الصناعية -- مستخلصات الأبحاث